Chemical and topographical patterns combined with solution shear for selective-area deposition of highly-aligned semiconducting carbon nanotubes. Issue 6 (22nd February 2021) - Dwyer, Jonathan H.; Suresh, Anjali; Jinkins, Katherine R.; Zheng, Xiaoqi; Arnold, Michael S.; Berson, Arganthaël; Gopalan, Padma
Abstract : Selective shear deposition of polymer-wrapped semiconducting carbon nanotubes (s-CNTs) into densely packed, highly aligned arrays of s-CNTs using removable chemical and topographical patterns. Abstract : Selective deposition of semiconducting carbon nanotubes (s-CNTs) into densely packed, aligned arrays of individualized s-CNTs is necessary to realize their potential in semiconductor electronics. We report the combination of chemical contrast patterns, topography, and pre-alignment of s-CNTs via shear to achieve selective-area deposition of aligned arrays of s-CNTs. Alternate stripes of surfaces favorable and unfavorable to s-CNT adsorption were patterned with widths varying from 2000 nm down to 100 nm. Addition of topography to the chemical contrast patterns combined with shear enabled the selective-area deposition of arrays of quasi-aligned s-CNTs (∼14°) even in patterns that are wider than the length of individual nanotubes (>500 nm). When the width of the chemical and topographical contrast patterns is less than the length of individual nanotubes (<500 nm), confinement effects become dominant enabling the selective-area deposition of much more tightly aligned s-CNTs (∼7°). At a trench width of 100 nm, we demonstrate the lowest standard deviation in alignment degree of 7.6 ± 0.3° at a deposition shear rate of 4600 s −1, while maintaining an individualized s-CNT density greater than 30 CNTs μm −1 . Chemical contrast alone enables selective-area deposition, but chemical contrast in addition to topography enables more effective selective-area deposition and stronger confinement effects, with the advantage of removal of nanotubes deposited in spurious areas via selective lift-off of the topographical features. These findings provide a methodology that is inherently scalable, and a means to deposit spatially selective, aligned s-CNT arrays for next-generation semiconducting devices.